Performance of OFDM System under Different Fading Channels and Channel Coding - Pratima Manhas; M. K. Soni (Institute of Advanced Engineering and Science, 2017)
Orthogonal frequency division multiplexing (OFDM) is a type of multicarrier modulation (MCM) technique in which larger bandwidth is divided into parallel narrow bands each of which is modulated by different subcarriers. All the subcarriers are orthogonal to each other and hence it reduces the interference among various subcarriers. OFDM technique is an efficient modulation technique used in certain wired and wireless application.In a wireless communication channel, the transmitted signal can travel from transmitter to receiver over multiple reflective paths. This results to multipath fading which causes fluctuations in amplitude, phase and angle of arrival of the received signal. For example, the signal which is transmitted from BTS (base transceiver station) may suffer multiple reflections from the buildings nearby, before reaching the mobile station. Such multipath fading channels are classified into slow fading/fast fading and frequency-selective/flat fading channels. This paper discusses the performance of OFDM system using various fading channels and channel coding. The parameter which is known as Bit error rate (BER) is calculated under different fading channels (AWGN, Rayleigh and Rician) for different digital modulation (BPSK, QPSK and QAM) and Channel coding (linear/Cyclic coding). Matlab Simulink tool is used to calculate the BER parameter.